2016
DOI: 10.1016/j.yhbeh.2016.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Behind melanocortin antagonist overexpression in the zebrafish brain: A behavioral and transcriptomic approach

Abstract: Melanocortin signaling is regulated by the binding of naturally occurring antagonists, agoutisignaling protein (ASIP) and agouti-related protein (AGRP) that compete with melanocortin peptides by binding to melanocortin receptors.ASIP overexpression in transgenic zebrafish results in alterations of dorso-ventral pigment pattern.We further demonstrate that ASIP overexpression results in increased growth but not obesity. The differential growth is explained by increased food efficiency and food intake levels, med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 65 publications
5
60
1
Order By: Relevance
“…Pharmacological studies in sea bass have shown that AgRP1 works as an inverse agonist at constitutively activated MC4R (Sánchez et al, 2009). In addition, ASIP1 overexpression working at central MC4R in transgenic zebrafish model results in enhanced feeding, feed efficiency, weight and linear growth but not in obesity (Guillot et al, 2016), in a similar way to the AgRP1 transgenic zebrafish (Song and Cone, 2007). Studies in zebrafish using first developmental stages demonstrated that AgRP1 knockdown results in reduced growth suggesting that AgRP1 suppression of MC4R activity is essential for larval growth (Zhang et al, 2012).…”
Section: Hypothalamic Neuropeptides Involved In the Control Of Food Imentioning
confidence: 97%
See 1 more Smart Citation
“…Pharmacological studies in sea bass have shown that AgRP1 works as an inverse agonist at constitutively activated MC4R (Sánchez et al, 2009). In addition, ASIP1 overexpression working at central MC4R in transgenic zebrafish model results in enhanced feeding, feed efficiency, weight and linear growth but not in obesity (Guillot et al, 2016), in a similar way to the AgRP1 transgenic zebrafish (Song and Cone, 2007). Studies in zebrafish using first developmental stages demonstrated that AgRP1 knockdown results in reduced growth suggesting that AgRP1 suppression of MC4R activity is essential for larval growth (Zhang et al, 2012).…”
Section: Hypothalamic Neuropeptides Involved In the Control Of Food Imentioning
confidence: 97%
“…Therefore, melanocortin system seems to impose a constitutive break to feeding and growth in fish probably through constitutive activity of MC4R. AgRP1 overexpression is the soundest response to fasting reported in fish, and its hypothalamic expression is essential to counteract MC4R negative effects on energy balance by inverse agonism on the receptor thus driving fish to feeding and concomitantly enhancing fish growth both dependently and independently on feeding levels (Guillot et al, 2016). In fact, AgRP1 mRNA abundance in hypothalamus increased in food deprived zebrafish (Song et al, 2003), goldfish (Cerdá-Reverter and Peter, 2003), sea bass (Agulleiro et al, 2013), and carp (Zhong et al, 2013) but not in Atlantic salmon (Murashita et al, 2009).…”
Section: Hypothalamic Neuropeptides Involved In the Control Of Food Imentioning
confidence: 99%
“…Fasting/food restriction decreases CART brain expression in Cypriniformes (goldfish Volkoff and Peter, 2001a, zebrafish Nishio et al, 2012; Guillot et al, 2016 and common carp, Wan et al, 2012), most Characiformes (red-bellied piranha Volkoff, 2014a, and pacu Volkoff et al, 2017), most Salmoniformes (Atlantic salmon, Murashita et al, 2009a; Kousoulaki et al, 2013, rainbow trout Figueiredo-Silva et al, 2012), Atlantic cod (Kehoe and Volkoff, 2007), cunner (Perciforme) (Babichuk and Volkoff, 2013), medaka (CART3) (Murashita and Kurokawa, 2011), and Siluriformes (channel catfish Kobayashi et al, 2008, African sharptooth catfish Clarias gariepinus Subhedar et al, 2011), suggesting an anorexigenic role for CART in teleost fish. Postprandial increases in CART brain expression have been shown in Senegalese sole (CART1a, CART 2a and CART4) (Bonacic et al, 2015), pacu (Volkoff et al, 2017), dourado (Volkoff et al, 2016), channel catfish (Peterson et al, 2012) but not in cod (Kehoe and Volkoff, 2007).…”
Section: Hormones Involved In Food Intakementioning
confidence: 99%
“…In mammals, the α-melanocyte-stimulating hormone (α-MSH, product of POMC) is an anorexigenic peptide that activates MC4R resulting in food intake inhibition (Loh et al 2015), while the antagonism of this receptor by AgRP exerts orexigenic actions (Rui 2013, Sohn 2015, Takeuchi 2016. Studies in cyprinids and salmonids (Kojima et al 2010, Zhang et al 2012, Dalmolin et al 2015, Guillot et al 2016 suggest that AgRP would counteract the basal inhibition of feeding induced by the melanocortin system (Kojima et al 2010, Zhang et al 2012, Dalmolin et al 2015, Guillot et al 2016.…”
Section: Short-term Signalling From Brainmentioning
confidence: 99%